Arabic Extensive Listening and ITS Language Learning Benefits - Rully Agung Yudhiantara; Syihabuddin Syihabuddin (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2023)
Foreign Language learning is a complex process that requires considerable effort from both teachers and learners, particularly in developing effective listening skills in foreign language classrooms. Among the various approaches, Extensive Listening (EL) has emerged as a promising pedagogical method for enhancing language acquisition. This research investigates the utilization of Extensive Listening (EL) as a pedagogical approach for teaching Arabic listening skills, focusing on its efficacy in facilitating vocabulary and grammar acquisition, as well as exploring students' perceptions regarding the benefits of language learning through EL. Language teachers often face challenges in cultivating listening skills among foreign language learners due to its inherent difficulty. The study employed observation, documentation, and focus group discussions as data collection methods, while data analysis involved several stages: data description, data reduction, and drawing conclusions. The findings reveal that EL was effectively integrated into the Arabic listening course, aligning with the course objectives and learning materials. Students actively engaged in grammar analysis through audiobooks and demonstrated a positive attitude towards EL, acknowledging its role in enhancing their vocabulary, pronunciation, and grammar knowledge.